Novel identification of Leishmania major in Hemiechinus auritus and molecular detection of this parasite in Meriones libycus from an important foci of zoonotic cutaneous leishmaniasis in Iran - Soheila Rouhani; Asad Mirzaei; Adel Spotin; Parviz Parvizi (Elsevier, 2014)
Summary: Background: One of the well-known foci of zoonotic cutaneous leishmaniasis (ZCL) in Iran is Turkemen Sahara, which is located in north eastern Iran. ZCL is a disease of mammals, and humans can become infected as accidental hosts. Many researchers have argued that Rhombomys opimus is the only main reservoir host of ZCL in this region of the Golestan province. No other rodents or mammals are thought to host or have been reported to host Leishmania parasites in this region. This research was designed and developed to isolate, detect and firmly identify Leishmania parasites in mammals and rodents other than R. opimus. Methods: Wild mammals were caught from gerbil burrows. Leishmania parasites were detected to assess the infection of reservoir hosts in 2010. Each genomic DNA sample was screened for Leishmania infection via nested PCR and sequencing using the internal transcribed spacer ribosomal DNA (ITS-rDNA) identification protocol for parasites. Results: The greatest number of infections (8/19) were found in Meriones libycus. One in three infections was found in Hemiechinus auritus, and this is the first report of infection in this species. Only Leishmania major was definitively identified and unambiguously typed in M. libycus and H. auritus. The infection rates in these two wild mammals were not significantly different, and no other gerbil parasites were detected in M. libycus or H. auritus at our study site. Conclusions: Recent findings of Leishmania turanica in R. opimus and failures to detect L. turanica in M. libycus may be attributable to unidentified Leishmania infections in two M. libycus due to unreadable sequences. These cases may represent mixed infections by L. major and L. turanica. The assumptions that gerbil parasites can be co-infectors provide a starting point for the identification of the causative and potential parasites responsible for the frequent infections that are mainly mediated via sandfly vectors. Keywords: Nested PCR, Hemiechinus auritus, ITS-rDNA, Leishmania major, Meriones libycus, Iran